Exosomal noncoding RNAs in gynecological cancers: implications for therapy resistance and biomarkers - Xu, Changfen; Xu, Peiyao; Zhang, Jiaqi; He, Sheng; Hua, Tingting; Huang, Aiwu (Frontiers in Oncology, 2024)
Gynecologic cancers, including ovarian cancer (OC), cervical cancer (CC), and endometrial cancer (EC), pose a serious threat to women's health and quality of life due to their high incidence and lethality. Therapeutic resistance in tumors refers to reduced sensitivity of tumor cells to therapeutic drugs or radiation, which compromises the efficacy of treatment or renders it ineffective. Therapeutic resistance significantly contributes to treatment failure in gynecologic tumors, although the specific molecular mechanisms remain unclear. Exosomes are nanoscale vesicles released and received by distinct kinds of cells. Exosomes contain proteins, lipids, and RNAs closely linked to their origins and functions. Recent studies have demonstrated that exosomal ncRNAs may be involved in intercellular communication and can modulate the progression of tumorigenesis, aggravation and metastasis, tumor microenvironment (TME), and drug resistance. Besides, exosomal ncRNAs also have the potential to become significant diagnostic and prognostic biomarkers in various of diseses. In this paper, we reviewed the biological roles and mechanisms of exosomal ncRNAs in the drug resistance of gynecologic tumors, as well as explored the potential of exosomal ncRNAs acting as the liquid biopsy molecular markers in gynecologic cancers.